Cancer-associated fibroblasts in pancreatic ductal adenocarcinoma - Zhang, Tianyi; Ren, Yanxian; Yang, Pengfei; Wang, Jufang; Zhou, Heng (Cell death & disease, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer with a prominent extracellular matrix (ECM) deposition and poor prognosis. High levels of ECM proteins derived from tumour cells reduce the efficacy of conventional cancer treatment paradigms and contribute to tumour progression and metastasis. As abundant tumour-promoting cells in the ECM, cancer-associated fibroblasts (CAFs) are promising targets for novel anti-tumour interventions. Nonetheless, related clinical trials are hampered by the lack of specific markers and elusive differences between CAF subtypes. Here, we review the origins and functional diversity of CAFs and show how they create a tumour-promoting milieu, focusing on the crosstalk between CAFs, tumour cells, and immune cells in the tumour microenvironment. Furthermore, relevant clinical advances and potential therapeutic strategies relating to CAFs are discussed.